Skill specific unemployment with imperfect substitution of skills - Runli Xie (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
A large body of literature explains the inferior position of unskilled workers by imposing a structural shift in the labor force skill composition. This paper takes a different approach by emphasizing the connection between cyclical variations in skilled and unskilled labor markets. Using a stylized business cycle model with search frictions in the respective sub-markets, I find that imperfect substitution between skilled and unskilled labor creates a channel for the variations in the sub-markets. Together with a general labor augmenting technology shock, it can generate downward sloping Beveridge curves. Calibrating the model to US data yields higher volatilities in the unskilled labor markets and reproduces stylized business cycle facts.
Keywords: E24; E32; J63; 330; business cycle; search frictions; skill specic unemployment; skill substitutability; Konjunkturelle Arbeitslosigkeit; Qualifikation; Faktorsubstitution; Arbeitsuche; Konjunkturtheorie; Theorie; USA